Community periodontal index of treatment needs and pain control beliefs in relation to calciumphosphate parameters and iron metabolism among hemodialysis patients - Książek, Katarzyna; Żołnierz, Joanna; Sak, Jarosław Jerzy (Polish Journal of Public Health, 2018)
Introduction. According to scientific reports, lack of oral hygiene, as well as disturbances in the calcium-phosphate and iron metabolism disorders are the main causes of periodontitis. The analysis of factors influencing the development and treatment of periodontitis should be conducted parallel in the medical and psychological domain.Aim. The aim of this study was to determine the dependency between the community periodontal index of treatment needs (CPITN) and the beliefs about pain control and biochemical parameters of the iron, calcium and phosphate metabolism.Material and methods. The study was conducted on a group of 124 hemodialysis patients with chronic renal failure aged from 24 to 90 (M=65.47; SD=15.65). The urea reduction rate (URR) was 71.24% and an average dose of dialysis (Kt/V) was 1.35. In the research time the indicators such as the values of serum levels of calcium and phosphorus, transferrin, ferritin, and iron were under control. Patients were diagnosed using the periodontal index of treatment needs (CPITN) and beliefs about pain control questionnaire (BPCQ) in Polish adaptation done by Z. Juczyński. In order to evaluate intergroup differences, the Kruskal-Wallis H test was used.Results. The hemodialysis patients with stage 2 or stage 3 periodontitis (according to CPITN) had the highest levels of transferrin and the lowest levels of ferritin (Table 3.). In contrast, the patients with stage 4 CPITN had the lowest level of transferrin and the highest level of ferritin. No statistically significant differences were observed between the five stages according to the community periodontal index of treatment needs (CPITN) in relation to the three domains of the beliefs about pain control questionnaire (BPCQ).Conclusions. The hemodialyzed patients with the most advanced periodontitis (stage 4 according to CPITN) had the lowest transferrin serum levels and the highest ferritin serum levels. They did not differ in pain control beliefs associated with the community periodontal index of treatment needs (CPITN).